2020
DOI: 10.4236/ajac.2020.112009
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene/MWCNT/Nafion Modified Glassy Carbon Electrode for the Electrochemical Determination of Caffeine

Abstract: Herein, a convenient method based on a fullerene/multiwalled carbon nanotube/Nafion modified glassy carbon electrode (fullerene/MWCNT/Naf/GCE) for the electrochemical determination of caffeine (CAF) is reported. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to study ionic exchange properties and conductivity the proposed electrode using [Fe(CN) 6 ] 3−/4− redox couple. Caffeine gave an irreversible oxidation peak around +1.33 V (vs. Ag/AgCl reference electrode) in HClO 4 (pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…[5,[11][12][13] However, the use of electrochemical sensors has increasingly attracted attention in recent years, due to attributes such as high stability, sensitivity, and selectivity. Compared with others, electrochemical methods are fast, inexpensive, miniaturizable, and offer good reproducibility, especially when the electrode is modified with materials including graphene oxide, [14] carbon nanotube, [15] conducting polymer, [16] clays, and organoclays. [17][18][19][20][21][22][23] Materials selected to be used in this study are organosmectite (since the raw clay is natural, abundant, and cheaper) and alizarin red S.…”
Section: Introductionmentioning
confidence: 99%
“…[5,[11][12][13] However, the use of electrochemical sensors has increasingly attracted attention in recent years, due to attributes such as high stability, sensitivity, and selectivity. Compared with others, electrochemical methods are fast, inexpensive, miniaturizable, and offer good reproducibility, especially when the electrode is modified with materials including graphene oxide, [14] carbon nanotube, [15] conducting polymer, [16] clays, and organoclays. [17][18][19][20][21][22][23] Materials selected to be used in this study are organosmectite (since the raw clay is natural, abundant, and cheaper) and alizarin red S.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the developed electrode was compared with that of previous studies, as shown in Table S1. , The developed p -PDMS-modified nanochannel electrodes show high sensitivity toward caffeine detection, with an LOD lower than most work reported before. Furthermore, the developed electrochemical sensors possess excellent anti-interference performance in real complex food samples.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the developed electrochemical sensors possess excellent anti-interference performance in real complex food samples. It has been reported that electrochemical detection of caffeine was easily affected by the food components such as dopamine, ascorbic acid, and l -dopa. ,, Without the interference of these substances, even a trace amount of caffeine could be detected in unprocessed samples by developed sensors. Although some studies have applied modified electrodes for real caffeinate sample analysis, the electrochemical curves in crude food were not displayed in these articles, making it hard to compare directly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The U.S. Food and Drugs Administration determined the maximal amount of CAF in soft drinks was approximately lower than 200 mg/L and specified the lethal dose only 10 g of CAF (about 170 mg/kg body weight) per people [11]. Since high concentration levels of CAF are toxic for human beings, it can lead to depression, hyperactivity, nausea and nervousness, heart diseases, kidney failure, asthma, vomiting, trembling, seizures, and DNA modification effects [12][13][14][15]. Therefore, developing a fast, sensitive, selective, and reliable method for analyzing CAF is an essential role in human health.…”
Section: Introductionmentioning
confidence: 99%